Contradiction in the Poems of Mikhail Lermontov - Marzieh Yahyapour; Janolah Karimi Motahhar; Masoumeh Mirzaie (مطالعات زبانی و بلاغی)
Poems by Mikhail Lermontov, poet of the Russia 19th century, still among the critics and litterateurs have a valuable place. In Russian literature, Lermontov is known as a despondent peccable and romantic poet. One of the prominent features of his poetry is a contradiction, contrast and distressing hesitation in understanding the concepts. Lermontov by his poems creates an annoying duality in the reader. In this article the exciting themes and prayers of the poet's poetry and their features is mentioned. During the years 1829 to 1839 he created four poems entitled "Molitva / Prayer". A distinctive feature of these poems is that the poet speaks to God in his own unique way ("My Prayer"). By examining his prayerful poems we find that the poet, sometimes stands up to the God, even with his bite and rebellious nature (Poems of 1829 and 1833). The impression is that the hero of the work is grumbling and confronting the God or has no desire to ignore the thirst for poetry and earthly desires. But the two poems of 1837 and 1839 differ from his earlier poems in the way of speaking to the Creator of being. In this article we compare poems related to prayer and Lermontov's four poems which are entitled Molitva. By examining Lermontov's poems of prayer, we come to the conclusion that the first two poems (entitled "Molitva") are in doubt and contradictory to the creator, but the next two poems (also called "Molitva") characterize the poet's poise before God. They represent and express the spirit of the seeker, the religious beliefs and the true form of worship of a religious person, and the mystical spirit of the poet is expressed in them. Examination of these poems illustrates how the hesitant poet reaches self-knowledge and then theology through nature.